Second Five-Year Plan (1956-61) North Arcot District (Madras State) - Planning Commission (Planning Commission, 1956)
The North Arcot district lies between 12° and 13° 15' of the northern latitude and 78° 25' and 79° 50' of the eastern longitude. It is bounded by the Chittoor district on the north, by the Chingleput district on the east, by the South Arcot district on the south and by the Salem and Chittoor districts on the west. This district has its headquarters at Vellore, a beautiful town surrounded by hills on all the four sides. There is a fort wherein are located all important Government offices of the district. This Fort is reported to have been built by the Vijayanagar Kings. It is built of well dressed cut stones without use of lime and mortar and it is considered to be an important piece of the medieval architecture.
Madras State